Does land transfer promote the development of new-type urbanization? New evidence from urban agglomerations in the middle reaches of the Yangtze River. (March 2022) - Zhang, Maomao; Tan, Shukui; Zhang, Yanwei; He, Ju; Ni, Qianlin
Highlights: A composite index system is established to evaluate China's new-type urbanization. The article studies new-type urbanization from the perspective of land transfer. The SDM model is used to explore the spatial spillover effects of new-type urbanization. The threshold panel model is used to discuss their nonlinear relationship. Abstract: With the rapid development of urbanization, land transfer has become a significant part of urban development. This article builds a comprehensive evaluation system to quantify the new-type urbanization level of urban agglomeration in the middle reaches of the Yangtze River from 2006 to 2017. To explore the relationship between the two more clearly, the spatial econometric model and the threshold panel model are used to explore how land transfer affects new-type urbanization. The results show that: the level of new-type urbanization is characterized by fluctuating increases, but that the regional differences show an expanding trend. The Moran's I of the new-type urbanization fluctuates at approximately 0.120, showing positive spatial correlation. The estimation results of the spatial Durbin model (SDM) indicate that the coefficient of land transfer and its spatial lag coefficient are 0.040 and 0.006 respectively, indicating that it has positive impacts on new-type urbanization. The results of the threshold panel model show that there is a significant nonlinear relationship between land transfer and new-type urbanization. The impacts of land transfer on the level of new urbanization will change in both positive and negative directions with changes in government intervention.